Utilization of Plastic Waste as Paver Block, Economic Potential, and Environmental Impact - Rachmawati, Lulu Millatina; Avianto, Luthfi Wigi; Mubarak, Luthfi Rizqi; Rasyid, Tazlila Rahmi; Suwandi, Suwandi; Suprayogi, Suprayogi; Utami, Amaliyah Rohsari Indah; Chandra, Indra (Journal of Community Research and Service, 2022)
One of the main factors that cause environmental damage in Indonesia is waste. Reducing waste by burning it directly without an incinerator will cause air pollution for the environment. CO2 is a substance produced by a complete combustion process. The amount of waste produced by Bandung Regency reaches 1,480.1 tons/day, with 20% of the waste being plastic waste. One way to utilize plastic waste is to recycle it into materials to produce paver blocks. Producing paver blocks requires a series of machines, such as crushing machines, plastic melting machines, and pressing machines. Plastic waste that has been sorted is put into a chopping machine and cut into 10 mm pieces. The plastic that has been cut is then melted down and printed, then re-pressed with a press machine. The type of plastic used in this research is polypropylene, with a melting point of 160-170°C. The size of the paver block produced is compatible with the market size. During the production of paver blocks, the CO2 concentration was monitored to see the effect of resin melting. In the analysis of paver blocks' economic potential, we found that the production cost using plastic waste is relatively expensive compared to conventional paver blocks. However, this type of paver block is not harmful to the environment. The results of this study indicate that plastic waste paver blocks can be used as paver block materials because they have quite an impact on the environment, although their economic value cannot compete with conventional paver blocks.